THE MEANING OF THE CIRCULAR FORMATION OF MOLULO DANCE IN THE CONTEXT OF LOCAL CULTURAL VALUES OF THE TOLAKI TRIBE - Nurachmy Sahnir (JURNAL PAKARENA, 2022)
Knowledge of the meaning contained in the Molulo dance performance relating to the context of the local cultural values of the Tolaki Tribe in Konawe Regency is contained in the floor pattern in this case a circular formation that contains a meaning based on "Kalo Sara" as a cultural symbol of the Tolaki tribe. The purpose of the study is to increase knowledge that there is a philosophy of life of the Tolaki tribe in the Molulo dance which is still maintained today. The descriptive method used by this study is to collect interview data, observation, and documentation. So that Lulo traditional dance by the Tolaki tribal community has a meaning related to local cultural values ranging from the form of movement of the position of hands and feet, the shape of the floor pattern, the displacement of dancers, and the change of dancers has a symbolic meaning in daily life by the Tolaki tribal community symbolized "Kalo sara" which is a circle pattern in the form of hand gestures and quadrangular patterns seen in the form of horizontal-vertical foot movements. The pattern that exists in Kalo sara, namely: circles, ties, and quadrangles have the local cultural value of the Tolaki tribe about unity and unity in the shape of the rattan circle, meaning the sincerity and purity of the white cloth, as well as the meaning of prosperity and well-being of the shape of the wicker container in which the rattan circle is placed. The conclusion of this study is about the meaning contained in the circular formation in the Molulo dance performance with the local cultural values of the Tolaki Tribe into several patterns of rules that must be obeyed